Laminate and method for manufacturing the same, and method for manufacturing polarizing film

By using a matrix layer containing organic cyclic structure polyol and thermoplastic polymer in polarized film production, the problem of excessive peeling between the matrix layer and the substrate is solved, and more stable polarized film transfer and higher yields are achieved.

JP2025052877APending Publication Date: 2025-04-07ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023161849
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

When producing polarized films, excessive peeling between the matrix layer and the substrate may lead to unstable transfer of the polarized film, resulting in a decrease in yield and the occurrence of "tunneling effect".

Method used

The adhesion between the matrix layer and the substrate is improved by controlling the Martin hardness difference of these materials and the content of thermoplastic polymers.

Benefits of technology

It effectively improves the adhesion between the substrate layer and the substrate, reduces unnecessary peeling, and improves the transfer stability and yield of the polarized film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025052877000001
    Figure 2025052877000001
Patent Text Reader

Abstract

To provide a laminate capable of improving adhesion between a base material and a resin layer.SOLUTION: A laminate includes a base material, and a resin layer formed of a resin containing an alicyclic structure-containing polymer and a thermoplastic polymer, wherein a difference HCOP-HRESIN between Martens hardness HCOP of the alicyclic structure-containing polymer and Martens hardness HRESIN of the resin is 10 N / mm2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a method for producing the same, and a method for producing a polarizing film. [Background technology]

[0002] In general, a polarizing film includes a polarizer layer and a resin layer provided on the surface of the polarizer layer. The resin layer can function as a protective layer that protects the polarizer layer. Such a resin layer can be produced, for example, by applying a coating liquid containing a material for the resin layer onto a substrate and drying the coating liquid (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2023-7352 A Summary of the Invention [Problem to be solved by the invention]

[0004] When a polarizing film is manufactured using a resin layer formed on a substrate, the resin layer is usually transferred to a polarizer layer. Specifically, the polarizer layer and the resin layer are bonded together, and the substrate is peeled off to obtain a polarizing film. Therefore, the substrate and the resin layer are required to be peelable. However, if the substrate and the resin layer are excessively prone to peeling off, peeling off may occur between the substrate and the resin layer at an unintended timing. If such unintended peeling occurs, it may be difficult to stably transfer the resin layer to the polarizer layer.

[0005] For example, a polarizing film may be manufactured by a method including laminating a long laminate having a substrate and a resin layer with a long polarizer layer while transporting them. In this case, the laminate and the polarizer layer may be pressed by two nip rolls arranged opposite to each other to laminate the laminate and the polarizer layer. In this case, if the substrate and the resin layer are prone to excessive peeling, partial peeling may occur between the substrate and the resin layer upstream of the nip rolls. When such peeling occurs, the peeled portion formed by the peeling may be formed so as to extend in the transport direction. Since this peeled portion is formed in a tunnel shape between the substrate and the resin layer, the peeling phenomenon may be called "tunneling". This tunneling may cause a decrease in the yield of the polarizing film, so it is desirable to suppress it.

[0006] The present invention has been devised in view of the above-mentioned problems, and an object of the present invention is to provide a laminate capable of improving adhesion between a substrate and a resin layer, a method for producing the same, and a method for producing a polarizing film using the laminate. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that a laminate including a substrate and a resin layer containing a combination of an alicyclic structure-containing polymer and a thermoplastic polymer, each of which has a Martens hardness that satisfies a specific relationship, can solve the above problems, thereby completing the present invention. That is, the present invention includes the following.

[0008] <1> A laminate comprising a substrate and a resin layer formed of a resin containing an alicyclic structure-containing polymer and a thermoplastic polymer; The Martens hardness H of the alicyclic structure-containing polymer COP and the Martens hardness H of the resin RESIN Difference H COP -H RESIN But 10N / mm 2 This is the laminate. <2> The Martens hardness H of the thermoplastic polymerTPP But 60N / mm 2 is less than <1> The laminate according to claim 1. <3> The amount of the thermoplastic polymer in the resin layer is 3% by weight or more and 20% by weight or less. <1> or <2> The laminate according to claim 1. <4> The thickness of the resin layer is less than 5 μm. <1> ~ <3> The laminate according to any one of claims 1 to 5. <5> <1> ~ <4> A method for producing the laminate according to any one of the preceding claims, applying a resin liquid containing the alicyclic structure-containing polymer, the thermoplastic polymer, and a solvent to the substrate; and drying the resin liquid applied to the substrate. <6> a polarizer layer; and <1> ~ <4> a step of bonding the resin layer of the laminate according to any one of the above items to the resin layer; and peeling off the substrate from the laminate. Effect of the Invention

[0009] According to the present invention, it is possible to provide a laminate capable of improving the adhesion between a substrate and a resin layer, a method for producing the same, and a method for producing a polarizing film using the laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims and their equivalents.

[0011] In the following description, "long" refers to a shape having a length that is usually 5 times or more, preferably 10 times or more, the width, specifically a shape having a length that can be wound into a roll for storage or transportation. The upper limit of the ratio of length to width is not particularly limited, but can be, for example, 100,000 times or less.

[0012] In the following description, unless otherwise specified, a "plate," a "layer," and a "film" may be a rigid member, or may be a flexible member such as a resin film.

[0013] In the following description, a layer is said to be "directly" on another layer means that the two layers are in contact with each other, and there are no other layers between the two layers, unless otherwise specified.

[0014] In the following description, the in-plane retardation Re of a certain layer is a value expressed by Re=(nx-ny)×d unless otherwise specified. In addition, the retardation Rth in the thickness direction of a certain layer is a value expressed by Rth=[{(nx+ny) / 2}-nz]×d unless otherwise specified. Here, nx represents the refractive index in the direction perpendicular to the thickness direction of the layer (in-plane direction) and giving the maximum refractive index. ny represents the refractive index in the in-plane direction of the layer and perpendicular to the direction of nx. nz represents the refractive index in the thickness direction of the layer. d represents the thickness of the layer. The measurement wavelength is 550 nm unless otherwise specified.

[0015] In the following description, unless otherwise specified, adhesives and pressure-sensitive adhesives are distinguished by their shear storage modulus. Specifically, unless otherwise specified, adhesives refer to materials having a shear storage modulus of 1 MPa to 500 MPa at 23°C after energy ray irradiation or heat treatment. Furthermore, unless otherwise specified, pressure-sensitive adhesives refer to materials having a shear storage modulus of less than 1 MPa at 23°C.

[0016] In the following description, unless otherwise specified, the term "(meth)acrylic resin" includes acrylic resin, methacrylic resin, and combinations thereof. Furthermore, unless otherwise specified, the term "(meth)acrylic acid" includes acrylic acid, methacrylic acid, and combinations thereof.

[0017] <1. Overview of the laminate> The laminate according to one embodiment of the present invention comprises a substrate and a resin layer. The resin layer is formed of a resin containing an alicyclic structure-containing polymer and a thermoplastic polymer. Thus, the resin layer contains the resin containing an alicyclic structure-containing polymer and a thermoplastic polymer, and usually contains only the resin. In the following description, the "substrate" and "resin layer" of the laminate according to this embodiment may be referred to as a "temporary substrate" and a "specific resin layer". In addition, in the following description, the resin forming the specific resin layer may be referred to as a "specific resin". Furthermore, in the following description, the laminate according to this embodiment comprising a temporary substrate and a specific resin layer may be referred to as a "transfer type laminate".

[0018] Martens hardness H of polymers containing alicyclic structures COP and the Martens hardness H of a specific resin RESIN Difference H COP -H RESIN is in a specific range. COP -H RESIN "Martens hardness difference" H COP -H RESIN A laminate satisfying such requirements can improve the adhesion between the temporary substrate and the specific resin layer.

[0019] A transfer laminate is usually used to provide a specific resin layer on a member (e.g., a polarizer layer) by a method including transferring the specific resin layer from a temporary substrate to the member. Specifically, a specific resin layer can be provided on the member by bonding a specific resin layer of a transfer laminate to a certain member and peeling off the temporary substrate. Here, the "transfer" of a certain layer refers to moving the layer from one member to another member, and includes both bonding the layer to the other member after peeling off the layer from one member, and bonding the layer on one member to the other member and then removing the one member. Therefore, when using the transfer laminate, a specific resin layer may be provided on the member after bonding a certain member to the specific resin layer of the transfer laminate, and then peeling off the temporary substrate. In addition, when using the transfer laminate, a specific resin layer may be provided on the member after bonding the specific resin layer to a certain member after peeling off the temporary substrate from the transfer laminate.

[0020] The transfer laminate according to this embodiment can have a high degree of adhesion to the extent that unintended peeling between the temporary substrate and the specific resin layer can be suppressed. Therefore, for example, the occurrence of tunneling due to unintended peeling can be suppressed. In addition, since this transfer laminate can usually easily peel off the temporary substrate, deformation and destruction of the specific resin layer due to peeling of the temporary substrate can be suppressed. Therefore, the specific resin layer can be smoothly transferred from the temporary substrate to another member, so that the transfer can be performed smoothly.

[0021] <2. Temporary base material> The temporary substrate is a member capable of supporting the specific resin layer, and may be, for example, a film, sheet, or plate formed of an appropriate material. From the viewpoint of improving the handleability of the transfer laminate, the temporary substrate is preferably a film.

[0022] The temporary substrate is usually formed of a resin. Therefore, the temporary substrate usually contains a resin, and preferably contains only a resin. The resin contained in the temporary substrate is preferably a thermoplastic resin. Hereinafter, in order to clearly distinguish between the resin contained in the temporary substrate and the specific resin contained in the specific resin layer, the resin contained in the temporary substrate may be referred to as the "substrate resin".

[0023] The base resin contained in the temporary substrate usually contains a polymer, preferably a thermoplastic polymer. In the following description, the polymer contained in the base resin may be referred to as a "first polymer". Examples of the first polymer include polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate; acrylic polymers such as polymethyl methacrylate; cellulose polymers such as triacetyl cellulose; polycarbonates; and the like, with polyolefins being preferred. The first polymer may be used alone or in combination of two or more types.

[0024] The content of the first polymer in the temporary substrate is preferably in a specific range relative to 100% by weight of the total amount of the temporary substrate. The range of the content of the first polymer is preferably 50% by weight or more, more preferably 70% by weight or more, particularly preferably 90% by weight or more, and is usually 100% by weight or less, preferably 99.95% by weight or less, more preferably 99.90% by weight or less. In addition, the range of the content of the first polymer in the base resin relative to 100% by weight of the total amount of the base resin may be the same as the above-mentioned range of the content of the first polymer in the temporary substrate relative to 100% by weight of the total amount of the temporary substrate. When the content of the first polymer is in the above-mentioned range, the rigidity of the temporary substrate can be increased to improve the handleability of the transfer laminate.

[0025] The base resin may further contain an optional component in combination with the first polymer. Examples of the optional component include stabilizers such as antioxidants, ultraviolet absorbers, and light stabilizers; resin modifiers such as lubricants and plasticizers; and antistatic agents. The optional components may be used alone or in combination of two or more.

[0026] The temporary substrate may have a single-layer structure with only one layer having the same composition, for example, the temporary substrate may have a single-layer structure with only one layer containing only the substrate resin.

[0027] The temporary substrate may also have a multi-layer structure comprising a plurality of layers having different compositions. Thus, the temporary substrate may have a multi-layer structure comprising, for example, a support layer formed of a certain resin and a release layer formed on the support layer of another resin. The release layer refers to a layer having a function of lowering the adhesion between the temporary substrate and the specific resin layer. Thus, the adhesion between the release layer and the specific resin layer formed directly on the release layer can be lowered compared to the adhesion between the support layer and the specific resin layer formed directly on the support layer. The release layer usually contains a release agent. Examples of the release agent include silicone-based release agents such as polydimethylsiloxane, fluorine-based release agents such as alkyl fluorides, and long-chain alkyl-based release agents such as polyolefins. When the temporary substrate has a release layer, the specific resin layer is usually provided on the release layer, so that the transfer laminate may have the specific resin layer, release layer, and support layer in this order. When the temporary substrate has the above-mentioned multilayer structure, the support layer may contain a substrate resin, the release layer may contain a substrate resin, or both the support layer and the release layer may contain a substrate resin.

[0028] The temporary substrate may have a long shape or a sheet shape.

[0029] The thickness of the temporary substrate is not particularly limited. In terms of a specific range, the thickness of the temporary substrate is preferably 25 μm or more, more preferably 30 μm or more, particularly preferably 38 μm or more, and is preferably 100 μm or less, more preferably 80 μm or less, particularly preferably 70 μm or less.

[0030] The above-mentioned temporary substrate may be manufactured, for example, by a method including forming the substrate resin into a film. Examples of the forming method include a melt forming method and a solution casting method. The film of the substrate resin thus obtained may be used as the temporary substrate, but the film may be subjected to a stretching process. Examples of the stretching process include a uniaxial stretching process in which a stretching process is performed only in one direction, and a biaxial stretching process in which a stretching process is performed in two different directions, and the biaxial stretching process is preferred. Furthermore, it is preferable to perform the stretching process slowly over a long period of time. The temporary substrate may also be manufactured, for example, by a method including forming a resin, further performing a stretching process as necessary to form a support layer, and forming a release layer on the support layer.

[0031] The temporary substrate may be a commercially available one purchased from the market. Examples of commercially available temporary substrates include biaxially oriented polypropylene film "New Type Torayfan BO40-2500" manufactured by Toray Industries, Inc. and polyethylene terephthalate films "Uni-Peel TR1", "Uni-Peel TR5", and "Uni-Peel TR6" manufactured by Unitika Co., Ltd.

[0032] <3.Specific resin layer> The specific resin layer is formed on the temporary substrate. Usually, the specific resin layer is formed directly on the temporary substrate. When the temporary substrate has a release layer, usually, the specific resin layer is formed directly on the release layer.

[0033] The specific resin layer is formed by a specific resin containing an alicyclic structure-containing polymer and a thermoplastic polymer. Therefore, the specific resin layer may contain a specific resin, or may contain only a specific resin. The specific resin is preferably a thermoplastic resin. Hereinafter, for the purpose of distinction, the alicyclic structure-containing polymer contained in the specific resin may be referred to as a "matrix polymer", and the thermoplastic polymer contained in the specific resin may be referred to as a "blended polymer". The matrix polymer may be used alone or in combination of two or more types. The blended polymer may be used alone or in combination of two or more types.

[0034] The combination of the base polymer and the compound polymer has a specific range of Martens hardness difference H COP -H RESIN Typically, the blend polymer is selected so that the Martens hardness H of the matrix polymer is COP Martens hardness H smaller than TPP Therefore, the specific resin containing the base polymer and the blended polymer has a Martens hardness H COP Martens hardness H lower than RESIN In this embodiment, the matrix polymer has a Martens hardness H COP and the Martens hardness H of a specific resin RESIN Difference H COP -H RESIN is within a certain range.

[0035] The Martens hardness difference H COP -H RESIN The specific range is usually 10N / mm 2 More than 12N / mm 2 More preferably, 15N / mm 2 That's all. Martens hardness difference H COP -H RESIN When the hardness is within the above range, the specific resin can be softer than the base polymer, so that the flexibility of the specific resin layer can be increased. Therefore, the stress applied to the transfer laminate during transportation and handling can be suppressed from concentrating on the interface between the temporary substrate and the specific resin layer, so that peeling due to the stress can be suppressed and adhesion can be increased. In addition, the tackiness of the specific resin layer is improved by improving the flexibility of the specific resin layer, which can also increase adhesion. Martens hardness difference H COP -H RESIN The upper limit is preferably 100 N / mm 2 Less than or equal to 80N / mm 2 Less than 60N / mm 2 The Martens hardness difference H COP -H RESIN When the thickness is equal to or less than the upper limit, it is possible to obtain a specific resin layer having high mechanical strength while improving the adhesion between the temporary substrate and the specific resin layer.

[0036] The Martens hardness of a resin such as a specific resin can be measured by the following method. A resin sample is dissolved in a solvent to obtain a solution. This solution is applied onto an appropriate support film and dried to obtain a film-like sample. The support film is attached to a slide glass with adhesive (e.g., Nitto Denko's "LUCIACSCS9861US") to fix the sample to the slide glass. The Martens hardness [N / mm 2 The measurement conditions may be a measurement temperature of 23° C., an indentation time of 20 seconds, and a creep time of 10 seconds. The indentation load is usually 0.3 mN, but may be appropriately changed depending on the hardness of the sample. For example, if the sample is too soft and an accurate Martens hardness cannot be measured with an indentation load of 0.3 mN, the indentation load may be reduced. Specific measurement conditions may be those described in the examples below.

[0037] The Martens hardness of a specific resin can be adjusted, for example, by the types and amounts of the alicyclic structure-containing polymer and the thermoplastic polymer.

[0038] The alicyclic structure-containing polymer as the base polymer has a repeating unit containing an alicyclic structure. This alicyclic structure-containing polymer usually has a low water vapor permeability. Therefore, the specific resin layer formed of the specific resin containing the alicyclic structure-containing polymer can function as a protective layer having a low water vapor permeability.

[0039] The alicyclic structure-containing polymer refers to a polymer containing an alicyclic structure in the molecular skeleton. The alicyclic structure-containing polymer may contain an alicyclic structure in the main chain, may contain an alicyclic structure in the side chain, or may contain an alicyclic structure in both the main chain and the side chain. Among them, from the viewpoint of mechanical strength and heat resistance, it is preferable that the alicyclic structure-containing polymer contains an alicyclic structure at least in the main chain.

[0040] Examples of the alicyclic structure include saturated alicyclic hydrocarbon (cycloalkane) structures, unsaturated alicyclic hydrocarbon (cycloalkene, cycloalkyne) structures, etc. Among these, from the viewpoints of mechanical strength and heat resistance, cycloalkane structures and cycloalkene structures are preferred, and cycloalkane structures are particularly preferred.

[0041] The number of carbon atoms constituting the alicyclic structure is preferably 4 or more, more preferably 5 or more, and is preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less, per one alicyclic structure. When the number of carbon atoms constituting the alicyclic structure is within this range, the mechanical strength, heat resistance, and moldability of the specific resin are highly balanced.

[0042] In the alicyclic structure-containing polymer, the ratio of the repeating unit containing the alicyclic structure can be appropriately selected according to the purpose of use.The ratio of the repeating unit containing the alicyclic structure in the alicyclic structure-containing polymer is preferably 55% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more.When the ratio of the repeating unit containing the alicyclic structure in the alicyclic structure-containing polymer is within this range, the transparency and heat resistance of the specific resin are good.

[0043] Examples of the polymer containing an alicyclic structure include a cycloolefin polymer, a vinyl alicyclic hydrocarbon polymer, and a hydrogenated product thereof, among which a cycloolefin polymer is preferred. The cycloolefin polymer refers to a polymer having a structure obtained by polymerizing a cycloolefin monomer. The cycloolefin monomer refers to a compound having a ring structure formed by carbon atoms and having a polymerizable carbon-carbon double bond in the ring structure. An example of the polymerizable carbon-carbon double bond is a carbon-carbon double bond capable of polymerization such as ring-opening polymerization. Examples of the ring structure of the cycloolefin monomer include a monocyclic ring, a polycyclic ring, a condensed polycyclic ring, a bridged ring, and a polycyclic ring formed by combining these rings.

[0044] Preferred examples of the cycloolefin polymer include norbornene-based polymers, monocyclic olefin-based polymers, cyclic conjugated diene-based polymers, and hydrogenated products thereof. Among these, norbornene-based polymers and hydrogenated products thereof have good transparency and moldability.

[0045] Examples of norbornene-based polymers and their hydrogenated products include ring-opening polymers of monomers having a norbornene structure and their hydrogenated products; addition polymers of monomers having a norbornene structure and their hydrogenated products. Examples of ring-opening polymers of monomers having a norbornene structure include ring-opening homopolymers of one type of monomer having a norbornene structure, ring-opening copolymers of two or more types of monomers having a norbornene structure, and ring-opening copolymers of a monomer having a norbornene structure and any monomer that can be copolymerized therewith. Examples of addition polymers of monomers having a norbornene structure include addition homopolymers of one type of monomer having a norbornene structure, addition copolymers of two or more types of monomers having a norbornene structure, and addition copolymers of a monomer having a norbornene structure and any monomer that can be copolymerized therewith. Examples of these polymers include polymers disclosed in, for example, JP-A-2002-321302.

[0046] Specific examples of norbornene-based polymers and hydrogenated products thereof include "ZEONOR" manufactured by Zeon Corporation; "ARTON" manufactured by JSR Corporation; and "TOPAS" manufactured by TOPAS ADVANCED POLYMERS.

[0047] The matrix polymer has a specific range of Martens hardness H COP It is preferable that the matrix polymer has a Martens hardness H COP The range is preferably 100N / mm 2 More preferably, 110N / mm 2 More preferably, 120N / mm 2 or more, preferably 190N / mm 2 Less than or equal to 180N / mm 2 Less than 170N / mm 2The Martens hardness H of the matrix polymer is as follows: COP In the case where the specific resin layer is used as a protective layer, the adhesiveness between the temporary substrate and the specific resin layer can be effectively improved.

[0048] Martens hardness H of the matrix polymer COP is the Martens hardness H of a particular resin RESIN The Martens hardness H of the base polymer can be measured in the same manner as that of the COP can be adjusted by factors such as the monomer composition of the matrix polymer and the degree of polymerization of the matrix polymer.

[0049] The matrix polymer has a specific range of indentation modulus E COP It is preferable that the matrix polymer has an indentation modulus E COP The range of the indentation elastic modulus E of the matrix polymer is preferably 1.0 GPa or more, more preferably 2.0 GPa or more, even more preferably 3.0 GPa or more, and is preferably 8.0 GPa or less, more preferably 6.0 GPa or less, even more preferably 4.0 GPa or less. COP When the hardness is within the above range, the adhesion between the temporary substrate and the specific resin layer can be effectively improved. The indentation modulus can be measured using a nanoindenter (Fisher Instruments' HM500) under the same measurement conditions as the above-mentioned Martens hardness measurement method. The indentation modulus E of the matrix polymer can be measured using a nanoindenter (Fisher Instruments' HM500) under the same measurement conditions as the above-mentioned Martens hardness measurement method. COP can be adjusted by factors such as the monomer composition of the matrix polymer and the degree of polymerization of the matrix polymer.

[0050] The range of the weight average molecular weight Mw of the base polymer is preferably 10,000 or more, more preferably 15,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 80,000 or less, particularly preferably 50,000 or less. When the weight average molecular weight of the base polymer is within such a range, the mechanical strength and moldability of the specific resin are highly balanced.

[0051] The molecular weight distribution (Mw / Mn) of the base polymer is preferably 1.2 or more, more preferably 1.5 or more, particularly preferably 1.8 or more, and is preferably 3.5 or less, more preferably 3.0 or less, particularly preferably 2.7 or less. Here, Mn represents the number average molecular weight. When the molecular weight distribution of the base polymer is equal to or more than the lower limit of the above range, the productivity of the base polymer can be increased and the manufacturing cost can be reduced. When the molecular weight distribution is equal to or less than the upper limit of the above range, the amount of low molecular weight components is reduced, thereby suppressing relaxation during exposure to high temperatures and improving the stability of the specific resin layer.

[0052] The weight average molecular weight (Mw) and number average molecular weight (Mn) can be measured using gel permeation chromatography (GPC). Solvents used in GPC include cyclohexane, toluene, and tetrahydrofuran. When using GPC, the weight average molecular weight can be measured as a relative molecular weight, for example, based on polyisoprene or polystyrene.

[0053] The content of the matrix polymer in the specific resin layer is preferably within a specific range relative to the total amount of the specific resin layer (100% by weight). The range of the content of the matrix polymer is preferably 70% by weight or more, more preferably 80% by weight or more, particularly preferably 85% by weight or more, and is usually 97% by weight or less, preferably 96% by weight or less, more preferably 95% by weight or less. In addition, the range of the content of the matrix polymer in the specific resin relative to the total amount of the specific resin (100% by weight) may be the same as the above-mentioned range of the content of the matrix polymer in the specific resin layer relative to the total amount of the specific resin layer (100% by weight). When the content of the matrix polymer is within the above-mentioned range, the adhesion between the temporary substrate and the specific resin layer can be effectively improved.

[0054] The thermoplastic polymer used as the blend polymer has a Martens hardness difference H COP -H RESINVarious kinds of thermoplastic polymers that fall within the above range can be used. Examples of blended polymers include polyesters, acrylic polymers, polyolefin polymers, and polymers containing an alicyclic structure. Among these, polyolefin polymers are preferred.

[0055] Examples of polyolefin polymers include low-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, poly-4-methyl-1-pentene, etc. Furthermore, the polyolefin polymers may be used alone or in combination of two or more kinds.

[0056] Martens hardness H of the blended polymer TPP The range is preferably 0.1 N / mm 2 More preferably, 1.0N / mm 2 More preferably, 5.0N / mm 2 More than 60N / mm 2 Less than 40N / mm 2 Less than 20N / mm 2 The Martens hardness H of the blended polymer is as follows: TPP When the thickness is within the above range, the adhesion between the temporary substrate and the specific resin layer can be effectively improved.

[0057] Martens hardness H of the blended polymer TPP is the Martens hardness H of a particular resin RESIN The Martens hardness H of the blended polymer can be measured in the same manner as that of the TPP can be adjusted by factors such as the monomer composition of the blended polymer and the polymerization degree of the blended polymer.

[0058] The blended polymer has the indentation modulus E of the matrix polymer. COP Lower indentation modulus E TPP It is preferable that the indentation modulus E of the blended polymer is TPPThe range is preferably 0.01 GPa or more, more preferably 0.05 GPa or more, even more preferably 0.1 GPa or more, and is preferably less than 1.0 GPa, more preferably 0.8 GPa or less, even more preferably 0.5 GPa or less. TPP When the indentation modulus is within the above range, the adhesion between the temporary substrate and the specific resin layer can be effectively improved. The indentation modulus of the blended polymer can be measured by the same method as the indentation modulus of the base polymer. The indentation modulus E of the blended polymer TPP can be adjusted by factors such as the monomer composition of the blended polymer and the polymerization degree of the blended polymer.

[0059] The weight average molecular weight Mw of the blended polymer is preferably in the same range as that of the base polymer. When the weight average molecular weight Mw of the blended polymer is in such a range, the mechanical strength and moldability of the specific resin are highly balanced.

[0060] The range of the molecular weight distribution (Mw / Mn) of the blended polymer is preferably the same as the range of the molecular weight distribution (Mw / Mn) of the base polymer. When the molecular weight distribution of the blended polymer is equal to or higher than the lower limit of the range, the productivity of the blended polymer can be increased and the manufacturing cost can be reduced. When the molecular weight distribution is equal to or lower than the upper limit of the range, the amount of low molecular weight components is reduced, thereby suppressing relaxation during exposure to high temperatures and improving the stability of the specific resin layer.

[0061] The content of the blended polymer in the specific resin layer is preferably within a specific range relative to 100% by weight of the total amount of the specific resin layer. The range of the blended polymer content is usually 3% by weight or more, preferably 4% by weight or more, more preferably 5% by weight or more, and usually 20% by weight or less, preferably 15% by weight or less, more preferably 13% by weight or less. In addition, the range of the blended polymer content in the specific resin relative to 100% by weight of the total amount of the specific resin may be the same as the range of the blended polymer content in the specific resin layer relative to 100% by weight of the total amount of the specific resin layer. When the blended polymer content is within the above range, the adhesion between the temporary substrate and the specific resin layer can be effectively improved. In detail, when the blended polymer content is equal to or more than the lower limit, the specific resin layer can be made flexible to enhance the adhesion. In addition, when the blended polymer content is equal to or less than the upper limit, the adhesion is usually suppressed from becoming excessive, and the temporary substrate can be smoothly peeled off.

[0062] The specific resin may further contain an optional component in combination with the base polymer and the blended polymer. The optional components include, for example, ultraviolet absorbers such as triazine-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and acrylonitrile-based ultraviolet absorbers; moisture absorbents; dispersants; organometallic compounds; stabilizers such as antioxidants and light stabilizers; resin modifiers such as lubricants and plasticizers; colorants such as dyes and pigments; and antistatic agents. The optional components may be used alone or in combination of two or more.

[0063] Indentation elastic modulus E of a specific resin RESIN and the indentation modulus of the matrix polymer E COP Difference with E COP -E RESIN is preferably in a specific range. COP -E RESIN The range is preferably 0.1 GPa or more, more preferably 0.2 GPa or more, even more preferably 0.3 GPa or more, and is preferably less than 3.0 GPa, more preferably 2.0 GPa or less, even more preferably 1.5 GPa or less.COP -E RESIN When the thickness is within the above range, the adhesion between the temporary substrate and the specific resin layer can be effectively improved.

[0064] Indentation elastic modulus E of a specific resin RESIN The range of the indentation elastic modulus E of the specific resin is preferably 1.0 GPa or more, more preferably 1.5 GPa or more, even more preferably 2.0 GPa or more, and is preferably less than 3.3 GPa, more preferably 3.1 GPa or less, even more preferably 2.9 GPa or less. RESIN When the indentation modulus is within the above range, the adhesion between the temporary substrate and the specific resin layer can be effectively improved. The indentation modulus of the specific resin can be measured by the same method as the indentation modulus of the matrix polymer. The indentation modulus E of the specific resin can be measured by the same method as the indentation modulus of the matrix polymer. RESIN can be adjusted, for example, by the composition of components in a specific resin such as the base polymer and the blended polymer.

[0065] The polymer molecules contained in the specific resin layer are preferably small in degree of orientation, and more preferably not oriented. When the degree of orientation of the polymer contained in the specific resin layer is small, the degree of entanglement of the polymer molecules can be increased, so that the toughness of the specific resin layer can be increased. In addition, when the degree of orientation of the polymer contained in the specific resin layer is small, the change in the polarization state of the polarized light caused by passing through the specific resin layer can usually be reduced, and preferably eliminated. Therefore, when the specific resin layer is bonded to the polarizer layer, the change in the polarization state caused by the specific resin layer can be suppressed, so that the control of the polarization state of the polarized light passing through the polarizing film including the specific resin layer and the polarizer layer can be simplified.

[0066] The degree of orientation of the polymer molecules contained in the specific resin layer can be represented by the optical anisotropy of the specific resin layer. Usually, when the degree of orientation of the polymer molecules is small, the optical anisotropy of the specific resin layer is small. Therefore, the specific resin layer preferably has small optical anisotropy in both the in-plane direction and the thickness direction, and more preferably has optical isotropy. In one example, the in-plane retardation of the specific resin layer at a measurement wavelength of 550 nm is preferably 5 nm or less, more preferably 4 nm or less, even more preferably 3 nm or less, and particularly preferably 2 nm or less. In one example, the retardation in the thickness direction of the specific resin layer at a measurement wavelength of 550 nm is preferably -5 nm or more, more preferably -4 nm or more, even more preferably -3 nm or more, and particularly preferably -2 nm or more, and is preferably 5 nm or less, more preferably 4 nm or less, even more preferably 3 nm or less, and particularly preferably 2 nm or less.

[0067] The specific resin layer is preferably transparent from the viewpoint of functioning as an optical film layer. Therefore, the specific resin layer preferably has a high total light transmittance. The specific resin layer preferably has a total light transmittance of 80% or more, more preferably 85% or more, and particularly preferably 90% or more. The total light transmittance can be measured using an ultraviolet-visible spectrometer in the wavelength range of 400 nm to 700 nm.

[0068] The specific resin layer usually has a single-layer structure having only one layer having the same composition. The temporary substrate may have a long shape or a sheet shape.

[0069] The specific resin layer is preferably thin. The specific thickness range of the specific resin layer is usually less than 5 μm, preferably 4.5 μm or less, more preferably 4 μm or less. When the specific resin layer is thin, peeling due to stress accumulated in the specific resin layer can be suppressed, so that the adhesion can be effectively improved. For example, when the specific resin layer is formed by a coating method, shrinkage stress generated during drying may remain in the specific resin layer. However, in a thin specific resin layer, such residual stress is small, so peeling due to the stress is unlikely to occur, and the adhesion can be increased. The lower limit of the thickness of the specific resin layer is not particularly limited, but is preferably 1 μm or more, more preferably 2 μm or more.

[0070] <4. Optional Layer> The transfer laminate may further include an optional layer in combination with the temporary substrate and the specific resin layer. For example, the temporary substrate may include an optional layer on the side opposite to the specific resin layer. However, it is preferable that the transfer laminate does not include any layer and includes only the temporary substrate and the specific resin layer.

[0071] <5. Adhesion between temporary substrate and specific resin layer> In the transfer laminate according to this embodiment, high adhesion can be obtained between the temporary substrate and the specific resin layer. The adhesion can be expressed by the peel strength as the force required to peel the temporary substrate from the specific resin layer. Specifically, the peel strength is preferably 0.20 N / 25 mm or more, more preferably 0.22 N / 25 mm or more, and particularly preferably 0.24 N / 25 mm or more. When the peel strength is equal to or more than the lower limit, peeling between the temporary substrate and the specific resin layer at an unintended timing can be suppressed. Thus, tunneling can be suppressed. The upper limit of the peel strength is preferably 1.5 N / 25 mm or less, more preferably 1.0 N / 25 mm or less, and particularly preferably 0.8 N / 25 mm or less. When the peel strength is equal to or less than the upper limit, the specific resin layer can be smoothly peeled off from the temporary substrate at a desired timing. Therefore, the transfer of the specific resin layer to the polarizer layer can be stably performed, and the polarizing film can be smoothly manufactured.

[0072] The peel strength can be measured by the following method. The specific resin layer of the transfer laminate is attached to a rigid flat plate (e.g., a glass plate) and fixed. A part of the temporary substrate is peeled off. The peeled part is pulled in a 90° direction (i.e., a normal direction to the main surface of the specific resin layer) at a peeling speed of 300 mm / min., and the peel strength is measured as the force required to peel off the temporary substrate. Specific measurement conditions may be those described in the examples below.

[0073] <6. Method for producing transfer laminate> The transfer laminate can be produced by a production method including a step (i) of applying a resin liquid containing a base polymer, a blended polymer, and a solvent to a temporary substrate; and a step (ii) of drying the resin liquid applied to the temporary substrate. This production method may be performed using a sheet of temporary substrate, but is preferably performed using a long temporary substrate. When a long temporary substrate is used, a long transfer laminate can be continuously produced. Hereinafter, this production method will be described in detail.

[0074] (Step (i) of applying resin liquid to temporary substrate) The method for producing the transfer laminate includes a step (i) of applying a resin liquid to a temporary substrate. As the temporary substrate, the above-mentioned materials can be used.

[0075] Since the resin liquid is a liquid material for forming a specific resin layer, it usually contains each component that can be contained in the specific resin layer. Specifically, the resin liquid contains a base polymer, a blended polymer, and a solvent, and may further contain any component that can be contained in the specific resin layer as necessary. A part or all of the base polymer, blended polymer, and any component contained in the resin liquid may be dissolved in a solvent. In addition, a part or all of the base polymer, blended polymer, and any component may be dispersed in a solvent.

[0076] As the solvent for the resin liquid, an organic solvent is usually used. Specific examples of the solvent include hydrocarbon solvents such as cyclohexane, alkylcyclohexane (methylcyclohexane, ethylcyclohexane, etc.), toluene, etc.; cyclic ether solvents such as tetrahydrofuran, etc. The solvent may be used alone or in combination of two or more.

[0077] The concentrations of the base polymer, the blended polymer, and the optional components in the resin liquid can be set as desired within a range in which the resin liquid has a viscosity suitable for coating. The total concentration range of the base polymer, the blended polymer, and the optional components is preferably 1% by weight or more, more preferably 5% by weight or more, particularly preferably 10% by weight or more, and is preferably 35% by weight or less, more preferably 30% by weight or less, particularly preferably 25% by weight or less.

[0078] Examples of methods for applying the resin liquid to the temporary substrate include curtain coating, extrusion coating, roll coating, spin coating, dip coating, bar coating, spray coating, slide coating, print coating, gravure coating, die coating, gap coating, and dipping.

[0079] (Step (ii) of drying the resin liquid applied to the temporary substrate) In step (i), the resin liquid is applied to the temporary substrate, thereby forming a layer of the resin liquid on the temporary substrate. Therefore, the method for producing a transfer laminate includes step (ii) of drying the resin liquid on the temporary substrate after the application of the resin liquid to the temporary substrate. By drying in step (ii), the solvent is removed from the layer of the resin liquid, and a specific resin layer containing the base polymer and the blended polymer, and which may further contain any optional components as necessary, is formed on the temporary substrate.

[0080] The temperature conditions for drying the resin liquid may vary depending on the type and amount of the base polymer, the blended polymer, and the solvent, but are generally preferably 70°C or higher, more preferably 80°C or higher, and particularly preferably 90°C or higher, and are preferably 140°C or lower, more preferably 130°C or lower, and particularly preferably 120°C or lower.

[0081] The drying time may vary depending on the type and amount of the base polymer, the blended polymer, and the solvent, but is generally preferably 30 seconds or more, more preferably 60 seconds or more, and particularly preferably 90 seconds or more, and is preferably 5 minutes or less, more preferably 4 minutes or less, and particularly preferably 3 minutes or less.

[0082] (Optional process) The method for producing a transfer laminate may further include any step in combination with the above steps (i) and (ii). For example, the method for producing a transfer laminate may include any step such as a step of trimming the produced transfer laminate, or a step of winding the produced transfer laminate into a roll.

[0083] <7. Manufacturing method of polarizing film> The above-mentioned transfer type laminate can be applied to a method for producing a polarizing film having a specific resin layer. For example, the transfer type laminate is A step (I) of bonding a polarizer layer and a specific resin layer of a transfer laminate; A step (II) of peeling off the temporary substrate of the transfer laminate; The method for producing a polarizing film including the steps of:

[0084] (Step (I) of bonding the polarizer layer and the specific resin layer) The method for producing a polarizing film includes a step (I) of bonding a polarizer layer and a specific resin layer of a transfer laminate. When bonding the polarizer layer and the specific resin layer before peeling off the temporary substrate, stress is applied to the transfer laminate including the temporary substrate and the specific resin layer, so that in the past, tunneling could occur due to unintended peeling off of the temporary substrate. However, the transfer laminate according to this embodiment can increase the adhesion between the temporary substrate and the specific resin layer, so that unintended peeling can be suppressed and bonding can be stably performed.

[0085] As the polarizer layer, a film that can transmit one of two linearly polarized lights whose vibration directions intersect at right angles and absorb or reflect the other can be used. Here, the vibration direction of linearly polarized light refers to the vibration direction of the electric field of the linearly polarized light. Such a film usually has a polarization transmission axis, can transmit linearly polarized light whose vibration direction is parallel to the polarization transmission axis, and can absorb or reflect linearly polarized light whose vibration direction is perpendicular to the polarization transmission axis.

[0086] The polarizer layer may be, for example, a film of a polyvinyl alcohol resin containing a vinyl alcohol-based polymer such as polyvinyl alcohol or partially formalized polyvinyl alcohol, which is subjected to appropriate treatments such as dyeing with a dichroic substance such as iodine, stretching, crosslinking, etc., in an appropriate order and by an appropriate method. The polarizer layer preferably contains a polyvinyl alcohol resin.

[0087] The thickness of the polarizer layer is preferably greater than 1 μm, more preferably greater than 2 μm, particularly preferably greater than 3 μm, and preferably less than 19 μm, more preferably less than 18 μm. When the thickness of the polarizer layer is greater than the lower limit, the optical performance of the polarizing film can be sufficiently improved. When the thickness of the polarizer layer is equal to or less than the upper limit, the warping of the display including the polarizing film can be reduced, and the bending recovery of the polarizing film can be effectively improved.

[0088] The specific resin layer and the polarizer layer may be bonded together via an adhesive, if necessary. Examples of the adhesive include acrylic adhesives, epoxy adhesives, urethane adhesives, polyester adhesives, polyvinyl alcohol adhesives, modified polyvinyl alcohol adhesives, polyolefin adhesives, modified polyolefin adhesives, polyvinyl alkyl ether adhesives, rubber adhesives, vinyl chloride-vinyl acetate adhesives, SEBS (styrene-ethylene-butylene-styrene copolymer) adhesives, ethylene adhesives such as ethylene-styrene copolymers, and acrylic ester adhesives such as ethylene-methyl (meth)acrylate copolymers and ethylene-ethyl (meth)acrylate copolymers. From the viewpoint of curing the adhesive in a short time, ultraviolet-curing adhesives are preferred as the adhesive, but from the viewpoint of making the adhesive layer thinner, polyvinyl alcohol or modified polyvinyl alcohol-based water-based adhesives may be used.

[0089] When the specific resin layer and the polarizer layer are bonded together using an adhesive, an adhesive layer is usually formed between the specific resin layer and the polarizer layer. The thickness of the ultraviolet curing adhesive layer is usually greater than 0 μm, preferably 0.1 μm or more, more preferably 1 μm or more, and preferably 5 μm or less, more preferably 3 μm or less. The thickness of the water-based adhesive is usually greater than 0 μm, preferably 0.02 μm or more, more preferably 0.04 μm or more, and preferably 0.1 μm or less, more preferably 0.08 μm or less. When the thickness of each adhesive layer is within the above range, a good appearance can be obtained, and the specific resin layer and the polarizer layer can be strongly bonded.

[0090] The specific method of bonding the polarizer layer and the specific resin layer is not particularly limited. For example, the long specific resin layer and the long polarizer layer may be bonded using a bonding tool such as a pinch roller, if necessary, via an adhesive. The specific resin layer may be bonded to only one side of the polarizer layer, or to both sides.

[0091] (Step (II) of peeling off the temporary substrate) The method for producing a polarizing film includes a step (II) of peeling off the temporary substrate. This step (II) may be performed before step (I) or simultaneously with step (I). From the viewpoint of particularly smoothly transferring the specific resin layer from the temporary substrate to the polarizer layer, it is preferable to perform step (II) after step (I). Usually, the adhesion between the temporary substrate and the specific resin layer is within an appropriate range that does not become excessive, so that the peeling off of the temporary substrate in step (II) can be performed smoothly. Therefore, deformation and destruction of the specific resin layer due to peeling off of the temporary substrate can be suppressed.

[0092] Usually, the peeling of the temporary substrate is carried out continuously. At this time, the peeling speed of the temporary substrate is preferably 70 m / min or less, more preferably 60 m / min or less, particularly preferably 50 m / min or less, from the viewpoint of effectively suppressing the breakage of the specific resin layer. The lower limit is not particularly limited, but is preferably 10 m / min or more, more preferably 15 m / min or more, particularly preferably 20 m / min or more, from the viewpoint of quickly proceeding with the production of the polarizing film.

[0093] (Step of providing an optional protective layer) In the method for producing a polarizing film, the specific resin layer may be provided on only one side of the polarizer layer by combining the above-mentioned steps (I) and (II), or the specific resin layer may be provided on both sides of the polarizer layer. When the specific resin layer is provided on only one side of the polarizer layer, an optional protective layer may be provided on the other side of the polarizer layer. Thus, the method for producing a polarizing film may include, as an optional step, a step of providing an optional protective layer on the surface of the polarizer layer opposite to the specific resin layer.

[0094] The optional protective layer may be formed, for example, by any thermoplastic resin other than the specific resin. As the optional thermoplastic resin, examples of resins having excellent transparency, mechanical strength, thermal stability and moisture shielding properties include acetate resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, cyclic olefin resins, (meth)acrylic resins, etc. Among them, (meth)acrylic resins and cyclic olefin resins are preferred because they provide a protective layer having high hardness and low water vapor permeability, and cyclic olefin resins having even lower water vapor permeability are more preferred. The optional protective layer may be, for example, ultra-thin bendable glass.

[0095] The thickness of the optional protective layer is not limited. For example, the thickness of the optional thermoplastic resin layer and the protective layer such as ultra-thin glass can be 13 μm to 100 μm.

[0096] The optional protective layer can be formed, for example, by a method including laminating an optional protective layer formed of an optional thermoplastic resin or an ultrathin glass to the polarizer layer via an adhesive as necessary. The adhesive used for laminating the polarizer layer and the optional protective layer can be the same as the adhesive used for laminating the specific resin layer and the polarizer layer. When an adhesive is used, an adhesive layer can be formed between the polarizer layer and the optional protective layer, and the thickness range of this adhesive layer may be the same as the thickness range of the adhesive layer formed between the specific resin layer and the polarizer layer.

[0097] The optional protective layer may be provided on the polarizer layer before the specific resin layer is provided. Also, the optional protective layer may be provided on the polarizer layer after the specific resin layer is provided. Furthermore, the optional protective layer may be provided on the polarizer layer simultaneously with the specific resin layer.

[0098] When the specific resin layer is provided on both sides of the polarizer layer, the temporary substrate does not need to be peeled off from one of the specific resin layers. In this case, the transfer laminate including the specific resin layer and the temporary substrate can be used as a protective layer. For example, a polarizing film including the specific resin layer / polarizer layer / transfer laminate in this order can be obtained.

[0099] (Step of Providing an Optional Adhesive Layer) The manufacturing method of the polarizing film may include a step of providing an adhesive layer as an optional step. The adhesive layer is usually provided as the outermost layer of the polarizing film. For example, the adhesive layer may be provided so that the polarizer layer, the specific resin layer, and the adhesive layer are arranged in this order in the thickness direction. Since the adhesive layer is formed by an adhesive, it can exert adhesive strength. Therefore, the polarizing film can be attached to other members by the adhesive strength of the adhesive layer. For example, when the polarizing film is incorporated into a display device having a display such as a liquid crystal panel and an organic electroluminescence panel (hereinafter, sometimes referred to as "organic EL panel"), the adhesive layer and the display can be attached to each other to provide the polarizing film on the display.

[0100] Examples of the adhesive include rubber-based adhesives, acrylic-based adhesives, polyvinyl ether-based adhesives, urethane-based adhesives, silicone-based adhesives, and polyolefin-based adhesives. Among them, acrylic-based adhesives and polyolefin-based adhesives are preferred from the viewpoint of heat resistance and productivity, and acrylic-based adhesives are particularly preferred. Moreover, the adhesive may be used alone or in combination of two or more types.

[0101] The thickness of the adhesive layer is preferably 2.0 μm or more, more preferably 5.0 μm or more, and preferably 30.0 μm or less, more preferably 25.0 μm or less, and particularly preferably 20.0 μm or less. When the thickness of the adhesive layer is equal to or more than the lower limit, the adhesive strength of the adhesive layer can be increased and the entrapment of air bubbles during lamination can be suppressed. When the thickness of the adhesive layer is equal to or less than the upper limit, the expansion and contraction behavior of the polarizing film can be suppressed, making it possible to make the film bezel-free.

[0102] The adhesive layer may be formed, for example, by coating an adhesive. The adhesive layer may also be formed, for example, by laminating an adhesive layer prepared in advance. There is no limitation on the timing of forming the adhesive layer. For example, when producing a polarizing film having a polarizer layer, a specific resin layer, and an adhesive layer in this order, the adhesive layer may usually be formed after the specific resin layer is formed on the polarizer layer.

[0103] (Step of providing an optional λ / 4 layer) The method for producing a polarizing film may include a step of providing a λ / 4 layer as an optional step. For example, when the polarizing film is used as an anti-reflection film for an organic EL panel, the λ / 4 layer may be provided between the polarizer layer and the organic EL panel. In this case, the polarizer layer, the specific resin layer, and the λ / 4 layer may be provided in the order of (polarizer layer) / (specific resin layer) / (λ / 4 layer), or in the order of (specific resin layer) / (polarizer layer) / (λ / 4 layer). In addition, an adhesive layer or a pressure-sensitive adhesive layer may be formed between each layer.

[0104] For example, when a λ / 4 layer is provided for a sunglass readable organic EL display or liquid crystal panel, the λ / 4 layer can be provided between the polarizer layer and the viewer. In this case, the polarizer layer, the specific resin layer, and the λ / 4 layer may be arranged in the order of viewer / (λ / 4 layer) / (polarizer layer) / (specific resin layer), or may be arranged in the order of viewer / (λ / 4 layer) / (specific resin layer) / (polarizer layer). In addition, an adhesive layer or a pressure-sensitive adhesive layer may be formed between each layer.

[0105] The λ / 4 layer has a specific range of in-plane retardation at a wavelength of 550 nm. Specifically, the in-plane retardation of the λ / 4 layer at a wavelength of 550 nm is preferably 110 nm or more, more preferably 120 nm or more, particularly preferably 125 nm or more, and is preferably 165 nm or less, more preferably 155 nm or less, particularly preferably 150 nm or less.

[0106] The slow axis of the λ / 4 layer preferably forms an angle of 40° to 50°, more preferably 42° to 48°, and particularly preferably 44° to 46° with respect to the polarization transmission axis of the polarizer layer. In this case, a circular polarizing plate can be obtained by combining the polarizer layer and the λ / 4 layer. Therefore, the polarizing film provided with the λ / 4 layer can function as a reflection suppression film when provided in a display device.

[0107] The λ / 4 layer preferably has inverse wavelength dispersion characteristics. The inverse wavelength dispersion characteristics refer to the property that the in-plane retardations Re(450) and Re(550) at measurement wavelengths of 450 nm and 550 nm satisfy Re(450) < Re(550). The λ / 4 layer having inverse wavelength dispersion characteristics can exhibit its optical function in a wide wavelength range.

[0108] The λ / 4 layer may be manufactured, for example, as a stretched film obtained by stretching a pre-stretched film formed of a suitable resin. Further, the λ / 4 layer may be manufactured, for example, as a liquid crystal cured layer in which a layer of a liquid crystal composition containing a suitable liquid crystalline compound is formed, the molecules of the liquid crystalline compound are aligned, and then the liquid crystal composition is cured. Among them, from the viewpoint of obtaining a thin and flexible polarizing film, the λ / 4 layer is preferably a liquid crystal cured layer. Such a λ / 4 layer as a liquid crystal cured layer can be manufactured, for example, by the method described in International Publication No. 2016 / 121602.

[0109] The λ / 4 layer may be formed, for example, by laminating previously prepared λ / 4 layers. For this lamination, an adhesive may be used as necessary. As the adhesive used for laminating the λ / 4 layer, the same adhesive as that which can be used for laminating the specific resin layer and the polarizer layer can be used.

[0110] In order to expand the viewing angle, the refractive index of the λ / 4 layer may be controlled to nx > nz > ny, or a positive C plate (nx = ny < nz) or a negative C plate (nx = ny > nz) called a viewing angle compensation layer may be laminated on the λ / 4 layer.

[0111] (Any other optional process) The method for producing a polarizing film may further include an optional step, if necessary. For example, the method for producing a polarizing film may include a step of providing an optional layer, such as a clear hard coat layer, an antiglare hard coat layer, an antireflection layer, an antistatic layer, an antifouling layer, or a conductive layer, on the polarizing film. The number of optional layers may be one layer or two or more layers. Furthermore, the position of the optional layer is not limited as long as it does not significantly impair the effect of the present invention.

[0112] The method for producing a polarizing film may also include, for example, a step of curing the adhesive. Usually, the step of curing the adhesive is carried out after the layers are bonded together using the adhesive. The adhesive curing method may be an appropriate method depending on the type of adhesive. For example, when an ultraviolet-curable adhesive is used, the adhesive can be cured by irradiation with ultraviolet rays.

[0113] Furthermore, the method for producing a polarizing film may include a step of trimming the polarizing film. For example, after a long polarizing film is produced using a long polarizer layer and a long transfer laminate, the polarizing film may be trimmed to a desired size.

[0114] (Polarizing film produced) Since the specific resin layer has high adhesion, the manufacturing method can bond the polarizer layer and the specific resin layer while suppressing unintended peeling of the temporary substrate. In addition, since the specific resin layer usually has an appropriate range of adhesion that does not become excessive, the peeling of the temporary substrate can be performed while suppressing deformation and destruction of the specific resin layer. Therefore, the transfer of the specific resin layer from the temporary substrate to the polarizer layer can be smoothly performed, so that a polarizing film having a polarizer layer and a specific resin layer can be smoothly manufactured.

[0115] The produced polarizing film may include any layer, as necessary, such as an adhesive layer, a protective layer, a pressure-sensitive adhesive layer, a λ / 4 layer, etc. For example, the polarizing film may include a protective layer, an adhesive layer, a polarizer layer, an adhesive layer, a specific resin layer, a λ / 4 layer, and a pressure-sensitive adhesive layer in this order.

[0116] Even if the specific resin layer is thin, the polarizer layer can be effectively protected, so that the polarizing film as a whole can usually be made thin. The thickness of the polarizing film is preferably 100 μm or less, more preferably 80 μm or less, and particularly preferably 70 μm or less. There is no particular limit to the lower limit of the thickness of the polarizing film, and for example, in applications where the display body is bent or folded, the thinner the film, the more preferable.

[0117] <8.Display device> The above-mentioned polarizing film may be provided, for example, in a display device. A display device including a polarizing film usually includes a display body in combination with the polarizing film. In this case, the polarizing film may be provided so as to include a specific resin layer and a polarizer layer in this order from the display body side. This display device may be manufactured, for example, by a manufacturing method including laminating a display body and a polarizing film. However, the manufacturing method of the display device is not limited thereto.

[0118] Examples of the display include a liquid crystal panel as a display for a liquid crystal display device, and an organic EL panel as a display for an organic electroluminescence display device (hereinafter, sometimes referred to as "organic EL display device" as appropriate). Usually, a polarizing film is provided on the viewing side of these displays.

[0119] A liquid crystal panel generally includes a liquid crystal cell including liquid crystal and electrodes capable of applying a voltage to the liquid crystal. The liquid crystal cell may be of any mode, such as an in-plane switching (IPS) mode, a vertical alignment (VA) mode, a multi-domain vertical alignment (MVA) mode, a continuous spin wheel alignment (CPA) mode, a hybrid alignment nematic (HAN) mode, a twisted nematic (TN) mode, a super twisted nematic (STN) mode, or an optically compensated bend (OCB) mode.

[0120] An organic EL panel usually includes an organic EL element including a transparent electrode layer, a light-emitting layer, and an electrode layer in this order. In this organic EL element, the light-emitting layer can emit light by applying a voltage from the transparent electrode layer and the electrode layer. Examples of materials constituting the organic light-emitting layer include polyparaphenylenevinylene-based, polyfluorene-based, and polyvinylcarbazole-based materials. The light-emitting layer may also include a laminate of layers with different light-emitting colors, or a mixed layer in which a layer of a dye is doped with a different dye. Furthermore, the organic EL element may include functional layers such as a hole injection layer, a hole transport layer, an electron injection layer, an electron transport layer, an equipotential surface forming layer, and a charge generation layer. EXAMPLES

[0121] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and may be modified and practiced as desired without departing from the scope of the claims and their equivalents.

[0122] In the following description, the units "%" and "parts" are by weight unless otherwise specified. Furthermore, the operations described below were carried out in air at room temperature and normal pressure (23°C, 1 atm) unless otherwise specified.

[0123] <Method for measuring Martens hardness and indentation elastic modulus> A solution was obtained by dissolving the polymer or resin to be used as a sample in an organic solvent (a mixed solvent of cyclohexane and ethylcyclohexane. Cyclohexane / ethylcyclohexane = 2 / 1 (weight ratio)). This solution was applied onto a polyethylene terephthalate film ("Uni-Peel" manufactured by Unitika Ltd.) and dried at 100°C to obtain a film-like sample with a thickness of 3 μm. The polyethylene terephthalate film was attached to a slide glass with adhesive ("LUCIACSCS9861US" manufactured by Nitto Denko Corporation) using a rubber roller to obtain a layer structure of "film-like sample / polyethylene terephthalate film / adhesive / slide glass".

[0124] The Martens hardness [N / mm 2 ] and indentation elastic modulus were measured. The indentation load was 0.03 mN for the polyolefin polymer ("Auroren 600S" manufactured by Nippon Paper Industries Co., Ltd.) and polyolefin polymer ("Auroren S-5419" manufactured by Nippon Paper Industries Co., Ltd.) used in Examples 1 and 2, and 0.3 mN for the other polymers and resins. "Auroren 600S" and "Auroren S-5419" are flexible, and there is a risk that the indenter will penetrate the sample if measured at 0.3 mN, so the indentation load was adjusted for accurate measurement. Other measurement conditions were as follows. Pressing time: 20 seconds Creep Time: 10 seconds

[0125] The measurements were carried out five times for each sample, and the average values ​​were used as the Martens hardness and indentation modulus of the sample.

[0126] <Method for measuring the thickness of a specific resin layer> The thickness of the specific resin layer was measured using an optical interference film thickness meter ("F20-EXR" manufactured by Filmet Co., Ltd.) The measurement conditions were as follows. Analysis range: 500nm~800nm Fourier Transform Mode Film structural model: air / n=1.53 (assuming specific resin layer) / PET (assuming temporary substrate) Specific resin layer thickness setting: 3μm±85%

[0127] <Peel strength measurement> A 25 mm wide double-sided tape (Teraoka Co., Ltd.'s "Shin Tape 7642") with a paper separator on one side was attached to the specific resin layer side of the transfer laminate with a rubber roller. The transfer laminate was cut to the width and length of the double-sided tape. The paper separator was peeled off from the double-sided tape. The transfer laminate was attached to a soda lime glass plate with a rubber roller via the double-sided tape.

[0128] About 30 minutes after the transfer laminate was attached to the soda lime glass, a 90-degree peel test was conducted to pull and peel off the temporary substrate of the transfer laminate. In this peel test, the temporary substrate was pulled at a 90° angle to the surface of the soda lime glass at a peel speed of 300 mm / min to measure the peel force (peel strength) required to peel off the temporary substrate. The peel force was measured using a peel force measuring instrument (IMADA "MX-500N-L550-E").

[0129] <Example 1> (Production of resin solution) A norbornene-based polymer (ZEONOR manufactured by Nippon Zeon Co., Ltd.; Martens hardness 124 N / mm) was used as the base polymer. 2 , indentation modulus 3.5 GPa), and a polyolefin polymer (Auroren 600S manufactured by Nippon Paper Industries Co., Ltd.; Martens hardness 6 N / mm 2 The matrix polymer and the blended polymer (0.1 GPa indentation modulus) were mixed in a blending ratio (weight ratio) of 90:10, and cyclohexane and ethylcyclohexane (solvent ratio of cyclohexane:ethylcyclohexane = 2:1) were further mixed as solvents to obtain a resin solution as a resin liquid. The total concentration of the matrix polymer and the blended polymer in the resin solution was 11 wt%. The resin solution was dried to obtain a specific resin sample, and its Martens hardness and indentation modulus were measured by the above-mentioned method.

[0130] (coating process) As a temporary substrate, a long polyethylene terephthalate film ("Unipeel" manufactured by Unitika Co., Ltd.) having a release layer made of an olefin resin on one side was prepared. The resin solution was applied to the smooth surface of the release layer side of this temporary substrate to form a layer of the resin solution. The layer of the resin solution was then dried at 100°C for 2 minutes to form a specific resin layer having a thickness of 3 μm on the temporary substrate. By the above operations, a transfer laminate including the temporary substrate and the specific resin layer formed on the temporary substrate was obtained. This transfer laminate was evaluated by the above-mentioned method.

[0131] <Example 2> The blended polymer was a polyolefin polymer (Auroren S-5419, manufactured by Nippon Paper Industries Co., Ltd.; Martens hardness 7N / mm 2 A laminate for transfer was produced and evaluated in the same manner as in Example 1, except that the compressive strength was changed to 0.2 GPa (indentation elastic modulus: 0.2 GPa).

[0132] <Comparative Example 1> A transfer laminate was produced and evaluated in the same manner as in Example 1, except that no blended polymer was used.

[0133] <Comparative Example 2> The compounded polymer was a cycloolefin polymer (Zeon Corporation's "ZNR1060R"; Martens hardness 125N / mm 2 A laminate for transfer was produced and evaluated in the same manner as in Example 1, except that the compressive strength was changed to 3.3 GPa (indentation elastic modulus 3.3 GPa).

[0134] <Comparative Example 3> The compounded polymer was a cycloolefin polymer (Zeon Corporation's "ZNR1060R"; Martens hardness 125N / mm 2 The transfer laminate was manufactured and evaluated in the same manner as in Example 1, except that the indentation elastic modulus was changed to 3.3 GPa (3.3 GPa indentation elastic modulus, ...

[0135] <Result> The results of the above-mentioned Examples and Comparative Examples are shown in the table below.

[0136] [Table 1]

[0137] <Consideration> As shown in Table 1, the results of the examples and comparative examples confirmed that the present invention makes it possible to realize a transfer laminate that can improve the adhesion between the temporary substrate and the specific resin layer.

Claims

1. A laminate comprising a substrate and a resin layer formed of a resin containing an alicyclic structure-containing polymer and a thermoplastic polymer; The Martens hardness H of the alicyclic structure-containing polymer COP and the Martens hardness H of the resin RESIN Difference H COP -H RESIN 10N / mm 2 This is the laminate.

2. The Martens hardness H of the thermoplastic polymer TPP , but 60N / mm 2 The laminate of claim 1 , wherein the thickness is less than 1 mm.

3. 2. The laminate according to claim 1, wherein the amount of the thermoplastic polymer in the resin layer is 3% by weight or more and 20% by weight or less.

4. The laminate according to claim 1 , wherein the resin layer has a thickness of less than 5 μm.

5. A method for producing the laminate according to any one of claims 1 to 4, comprising the steps of: applying a resin liquid containing the alicyclic structure-containing polymer, the thermoplastic polymer, and a solvent to the substrate; and drying the resin liquid applied to the substrate.

6. A step of bonding a polarizer layer and the resin layer of the laminate according to any one of claims 1 to 4; and peeling off the substrate from the laminate.

Citation Information

Patent Citations

  • Laminate and method for manufacturing the same, and method for manufacturing polarization film

    JP2023007352A